PEMBELAJARAN INKUIRI DENGAN THINKING MAPS PADA PEMBELAJARAN FISIKA - Yuliati, Lia; Kusaeri, Sentot; Munfaridah, Nuril (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2016)
Inquiry-based learning has been proven to be one of the effective types of learning although adjustment is still needed, for example by using thinking maps as supplementary learning tool. The purpose of this research was to develop inquiry-based learning model with thinking maps for physics learning. Inquiry-based learning model with thinking maps was developed with 4D model. Research was conducted at three high schools in Malang-East Java. Students were divided into three experimental and control classes. Instruments used were written test and interview guideline. Results showed that students who received inquiry learning with thinking maps achieved better test score than control classes. In addition, studentsâ answer analysis showed that they also have better higher-order thinking skills than students in the control class. Therefore, inquiry-based learning with thinking maps was found to be effective to use in physics learning.